Herbarium Areqvipense (HUSA): computerization and representativeness of its collection - Treviño, Italo F. (2012)
Scientific collections and herbaria are essential sources of information and education for researchers and practitioners in biological sciences. The Herbarium Areqvipense (HUSA), registered at Index Herbariorum since 2004, holds one of the most important collections in Peru. In this paper we provide information about the collection, and its representativeness for the Peruvian flora. HUSA has more than 11000 specimens recorded to date, with more than 2300 determined species, consisting mostly of Magnoliophyta and Pteridophyta (ca. 98%), and a smaller proportion of Basidiomycetes, Ascomycetes (fungi and lichens) and Bryophyta (mosses). The collection includes specimens from 23 departments of Peru, where the samples belonging to Arequipa have the largest number of individuals collected (3375) accounting for 31% of the collection. Asteraceae and Solanaceae are the most collected with 1571 and 964 specimens, respectively. The majority of geo-referenced specimens came from the tropical wet forest with 15%, followed by the tropical pre-montane wet forest with 8%. We also provide a list of the nomenclatural types and a brief summary of the history and development of HUSA since its creation.